Conhecer o professor através dos seus alunos: O desenvolvimento profissional de um futuro professor de Educação Física - Ricardo Nuno Gonçalves da Silva (2020)
Discovering the teacher through his students: the professional development of a future Physical Education teacher is the document prepared by an intern in the Physical Education discipline who reports, through a personal speech, the main events, difficulties and achievements of their supervised teaching practice. The internship reports transmit the personal perspective of an intern who faced with the teaching-learning for the first time by assigning the teacher role. This document is grounded by a professional development framework based on the reflexive problems-based learning common to a teaching professional who is in his last year of formation. Throughout this document, we can see an evolution through the time of the beliefs and skills of the intern student in relation to his teaching conception, application of teaching models and activities that are part of the teacher's daily life. All these topics will be develop based on the problems and potentialities of a teacher who has the desire to become a Physical Education teacher.